The Legal Standing of Pancasila in the Practice of Judicial Review of Legislation Against the Constitution in Indonesia - Reisa Malida (NEGREI: Academic Journal of Law and Governance, 2025)
This article examines the legal position of Pancasila in the practice of judicial review of legislation in Indonesia, particularly in relation to the 1945 Constitution. Drawing upon Hans Kelsen's Stufenbau theory and its further development by Hans Nawiasky, the study places Pancasila at the apex of the normative hierarchy as the grundnorm or staatsfundamentalnorm. Through doctrinal legal research, the article analyzes how Pancasila functions not only as a symbolic foundation of the state but also as a meta-juridical norm that guides the formation, interpretation, and evaluation of statutory law. The analysis shows that although the Constitutional Court has applied Pancasila both as the state foundation and as part of the Constitution through its inclusion in the Preamble, such dual treatment risks weakening its role as the highest legal norm. This article argues that in order to maintain the status of Pancasila as the grundnorm, judicial review should refer to it as the highest normative reference, not simply as a textual component of the Constitution. This perspective ensures a more substantive and coherent legal framework that upholds the foundational principles of the Indonesian legal system. Keywords: Pancasila, constitutional review, grundnorm, Constitutional Court, legislative hierarchy, Indonesian legal system